THE EFFECT OF SELF REGULATED LEARNING ON ACADEMIC BOREDOM OF STUDENT AT SMP MUHAMMADIYAH 9 BOARDING SCHOOL TANGGULANGIN - Widiyanti, Widiyanti; Ghozali Rusyid Affandi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the influence of self-regulated learning on academic boredom among students at SMP Muhammadiyah 9 Boarding School Tanggulangin. Method: Utilizing a quantitative approach with simple linear regression analysis, data were collected from 105 male and female students using two instruments: the Self-Regulated Learning Scale adapted from the Short Self Regulation Questionnaire (SSRQ) by Carey, Neal, and Collins (2004), and the Academic Boredom Scale adapted from The Academic Boredom Survey Instrument (ABSI) developed by Sharp et al. Results: The analysis revealed that self-regulated learning has a significant effect on academic boredom, with an R Square value of 0.164, indicating that 16.4% of the variance in academic boredom can be explained by students' self-regulated learning. The remaining 83.6% is influenced by other factors. Novelty: This study contributes to the limited research on the psychological dynamics of boredom in boarding school environments by highlighting the role of self-regulatory strategies in mitigating academic disengagement, offering insights for educators to develop interventions that foster student autonomy and engagement in structured learning settings.